Taxonomic Notes on Brachyuran Crab Jonas indicus Chopra, 1935 of Andhra Pradesh Coastal Waters - Kumar, Ponnada Vijay; Kumar, Virendra; Babu, D.E; Tarapatla, Pradeep Sastry; Tenali, Diamond Rajakumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Marine crab species Jonas indicus carapace is longitudinally elliptical and its dorsal surface is set with clusters of granules. The rostrum is bidentate and the rostral spine is produced beyond the tip of the pre-orbital spines. The lateral border of the carapace is with sharp teeth. The flagellum of the antenna is longer than half the length of the carapace. The dactylus of the last pair of ambulatory legs is flattened and paddle-shaped. The body is pinkish-white in colour. Present taxonomic reports based on collected specimens from Kaviti, Visakhapatnam, Kakinada, Machilipatnam, and Vodalarevu landing centers of the Andhra Pradesh coastal region.